Synthesis of Enantioenriched Azaborole Helicenes by Chirality Transfer from Axially Chiral Biaryls - Full, Felix; Wildervanck, Martijn J.; Volland, Daniel; Nowak-Król, Agnieszka (Synlett, 2022)
We report the enantioselective synthesis of azaborole helicenes from enantioenriched axially chiral precursors. The borylation/metal-exchange reaction sequence affords the target compounds with full transfer of chirality from the corresponding biaryls. Experimental studies provided insights into the configurational stability of the heterobiaryls and their (chir)optical properties. The structure of the phenyl-substituted helicene was unambiguously confirmed by single-crystal X-ray analysis.
Keywords: axial chirality; azaboroles; borylation; chirality transfer; helicenes; configurational stability